Gas/liquid separation in an I-SEP cyclone - Allstaff, E. J. (Cranfield University, 2002)
An extensive experimental programme tested an l-SEP unit with air and water. This provided data on the separation efficiency and pressure drop across the l- SEP, as they varied with changing inlet conditions, geometry and outlet restrictions. The main conclusion from this work is that the resistance on the outlets directly affects the efficiency of the separator. Although it is possible to optimise the performance by changing 'the geometry, a small change in inlet conditions, common in oil and gas applications, causes the performance to change. _By using an identified relationship between the differential pressure and the operating conditions, an optimum performance over a much wider range of inlet conditions can be achieved. This work has contributed to the field of gas/liquid separation in axial-flow cyclones by demonstrating that manipulating the differential pressure between the outlets can control the separation efficiency. The relationship developed between the optimum differential pressure and the inlet conditions has not been identified in any of the literature available at the time of this work.